Determining the effect of glucagon-like peptide 1 (GLP-1) upon skeletal muscle metabolism and blood flow in older age - Jandova, Tereza (2017)
Age-related musculoskeletal and metabolic disorders often resulting from glucose intolerance due to age-related insulin resistance represent one of the most significant health problems in our ageing world. The incretin hormone glucagon-like peptide-1 (GLP-1) has shown to have positive effects on vascular function and glucose disposal as demonstrated by recent human and animal studies. This study, therefore, aimed to investigate whether GLP-1 can exert the same positive effect on muscle’s postprandial glucose metabolism and vascular blood flow in old age. To examine such effects, the study was conducted in a cross-over design (± GLP-1) consisting of two acute study visits with a four week ‘wash-out’ period. GLP-1 was infused in the femoral artery in overnight fasted healthy old volunteers (n=7) along with glucose and insulin clamps in combination with Octreotide and amino acids to achieve constant postprandial conditions. Leg blood flow (LBF) was measured by Doppler ultrasound, computation of rates of total body glucose metabolism (M) during the clamps was calculated by glucose infusion rates minus urinary loss of glucose minus space correction and leg glucose disposal by arterial-venous (A-V) balance technique. Our results show that the infusion of GLP-1 increased overall LBF, which was significant when a t-test was applied (P < 0.05) but not significant using a 2-way ANOVA. Significant increases (P < 0.05) were also seen in measured whole body glucose metabolism (M). However, glucose leg uptake during the GLP-1 infusion did not significantly increase. We, therefore, conclude that GLP-1 infusion in healthy old people has a significant effect on whole body postprandial glucose metabolism and vascular blood flow. However, this effect may be influenced by raised insulin concentrations and exerted possibly through an insulin-mediated mechanism and not by GLP-1 action alone. Nevertheless, GLP-1 effect could still contribute to the increased delivery of glucose to the muscle in the elderly and specifically combat the negative consequences of ageing i.e. impaired glucose uptake, vascular blood flow and age-related insulin resistance by further enhancing the action of insulin. However, further investigations are required.